The scientific history of hydrocephalus and its treatment - Aschoff, Alfred; Kremer, Paul; Hashemi-Kalibar, Seyed-Bahram; Kunze, Stefan (Neurosurgical review, 1999)
Hydrocephalus cases were regularly described by Hippocrates, Galen, and early and medieval Arabian physicians, who believed that this disease was caused by an extracerebral accumulation of water. Operative procedures used in ancient times are neither proven by skull findings today nor clearly reported in the literature. Evacuation of superficial intracranial fluid in hydrocephalic children was first described in detail in the tenth century by Abulkassim Al Zahrawi. In 1744, LeCat published findings on a ventricular puncture.
Gesehen am 05.05.2021